Cultivating Peace through Education: A Case Study of Social Studies in Aceh’s Junior High Schools - Halik, Halik; Yusuf, Rusli; Idris, Jamaluddin; Darusman, Darusman; Sahlan, Muhammad; Fazal, Khairil; Rusdi, Mikdar (Jurnal Ilmiah Peuradeun, 2025)
Aceh, a post-conflict region in Indonesia, continues to face challenges in fostering social cohesion and reconciliation through education. Despite its crucial role in peacebuilding, peace education remains insufficiently integrated into the formal curriculum. This study investigated the systematic incorporation of peace education within the junior high school Social Studies curriculum in Aceh through a Research and Development (R&D) design. The research consisted of three phases: (1) curriculum mapping to identify opportunities for peace-related themes, (2) development of a structured peace education module, and (3) evaluation of its effectiveness through classroom observations, focus group discussions (FGDs), interviews, and pre- and post-tests involving 70 students and 9 teachers in Pidie Regency. Findings showed that values such as tolerance, mediation, and conflict resolution are implicitly present in existing materials but lack structured pedagogical integration. The developed module, validated by experts and teachers, significantly improved students’ understanding of peace concepts, empathy, and conflict resolution skills. Embedding peace education into existing curricula, rather than introducing it as a separate subject, proved more sustainable and contextually effective. The study highlighted the importance of comprehensive teacher training and supportive policy frameworks to enable large-scale implementation, this research supports Sustainable Development Goals (SDG 4 and SDG 16), advancing quality education, peace, and strong institutions. The model offers a scalable framework for integrating peace education into Social Studies curricula in other post-conflict regions.